Rent Extraction and Prosocial Behavior - Tobias Cagala; Ulrich Glogowsky; Veronika Grimm; Johannes Rincke; Amanda Tuset-Cueva (Center for Economic Studies and ifo Institute (CESifo), 2019)
We present controlled experimental evidence on how rent extraction by an administrator affects giving to non-profit associations. Holding the price of giving constant, we compare contributions between two conditions: a rent extraction condition, in which an administrator can expropriate a part of the contributions and a control condition without rent extraction. We find that rent extraction strongly reduces average contributions. Studying the channels through which this effect operates, we demonstrate that rent extraction has situational spillovers, suggesting that it undermines the contributors' general preference for giving. In contrast, we do not find evidence for negative reciprocity towards the administrator.
Keywords: D02; D03; H41; 330; rent extraction; donations; prosocial behavior